A Case Study on Executive–Legislative Conflict in the Amendment of the Corruption Eradication Commission (KPK) Law in Indonesia - Markus Pattiradjawane; Yohanes Latuconsina; Michael Soplanit; Samuel Souisa; Maria Latuconsina; Angel Pattiradjawane; Jessica Lestaluhu (Journal of Multidisciplinary Law Studies, 2026)
The amendment of Indonesia’s Corruption Eradication Commission (KPK) Law has triggered constitutional controversy concerning the distribution of power between the executive and legislative branches and its implications for institutional independence. This study examines the nature of executive–legislative conflict arising from the legislative process of the KPK Law revision, focusing on constitutional principles of checks and balances and separation of powers. Using a qualitative case study approach, this study examines legal documents, parliamentary records, Constitutional Court decisions, and scholarly literature to critically analyze executive–legislative relations and constitutional tensions arising from the amendment process. The findings reveal that the amendment process was heavily influenced by political interests that overshadowed constitutional safeguards intended to preserve the independence of anti-corruption institutions. The legislative process demonstrated a strong dominance of the House of Representatives (DPR) in initiating and approving the amendment, while the executive branch played a facilitating and endorsing role. This condition has raised concerns regarding the weakening of the KPK’s independence and the potential imbalance in the anti-corruption framework. Furthermore, public and institutional responses reveal significant constitutional tensions, particularly regarding the interpretation of state authority in corruption eradication efforts. This study concludes that the amendment of the KPK Law represents a substantial shift in Indonesia’s constitutional equilibrium, in which executive–legislative political alignment has weakened the effectiveness and independence of anti-corruption institutions. Strengthening constitutional safeguards and ensuring clearer delineation of institutional authority are essential to maintain democratic accountability and the rule of law in Indonesia.